Pengaruh Ion Doping Zn pada Sifat Kemagnetan Barium M-Heksaferit BaFe12-xZnxO19 berbasis Pasir Besi Tulungagung: Linda Silvia, Kurniawati Choirur Rosyidah, Mohammad Zainuri - Linda Silvia, Linda Silvia; Kurniawati Choirur Rosyidah, Kurniawati Choirur Rosyidah; Mochamad Zainuri, Mochamad Zainuri (Jurnal Fisika dan Aplikasinya, 2025)
In this paper we report on the effect of doping Zn ions on magnetic properties of Barium M-Heksaferit (BAM) (BaFe12-xZnxO19) based on iron sand from Tulungagung. Synthesis of Barium M-Heksaferit powder by using coprecipitation method with ingredients from local iron sands. The experiments carried out by controlling the concentration of Zn with variation of x = 0, 0.3, and 0.7 with the calcination temperature 10000 C. Characterization of the samples was done by XRD, VSM (Vibrating Sample Magnetometer), and SEM. XRD was used for BAM phase identification, where BAM phase formed on calcination temperature 10000 C. The variation of doping obtained for BAM without doping field coercivity 0.09 T and remanensi magnetic 7.72 emu/g and for the doping concentration x = 0.3 field coercivity 0.04 T and magnetic remanensi 11.81 emu/g, where the value of the coercivity field and magnetization remanensi BAM particles varies depending on the concentration of doping ions were added. BAM particles formed hexagonal structure with an average particle size of ± 1 um.